The Influence of Management Information System Integration and Personnel Data Management on the Effectiveness of Leadership Decision-Making at Disinfolahtaau - Iswarini, Windi (Dinasti International Journal of Digital Business Management, 2025)
This study aims to analyze the impact of the integration of personnel management information systems and data management on the effectiveness of decision-making by leaders at Disinfolahtaau. A quantitative research approach was employed, with data collected from 51 respondents using structured questionnaires. The results of the validity and reliability tests showed that all research instruments were valid and reliable. The normality test indicated that the data were normally distributed, while multicollinearity and heteroscedasticity tests confirmed the absence of any violations in the regression model. The findings from multiple linear regression analysis revealed that both the integration of management information systems (X1) and personnel data management (X2) significantly and positively affect decision-making effectiveness (Y). The regression equation Y=1.256+0.412X1+0.530X2 indicates that personnel data management has a stronger influence. The coefficient of determination (R²) of 0.82 shows that 82% of decision-making effectiveness is explained by these variables. The simultaneous F-test confirmed the significant combined influence of X1 and X2. These findings emphasize the importance of integrating technology and optimizing data management to enhance organizational decision-making. Future research should explore other contributing factors such as organizational culture and leadership styles.